Atomistic simulations to study the effects of helium bubbles on crack tip behavior in single crystal Ni. (30th June 2021) - Sharma, Saurabh S; Parashar, Avinash
Abstract: Safety of nuclear reactors is an issue that constantly hovers in the mind of the designers. Helium embrittlement in nickel-based alloys poses challenges hitherto unfathomed in the nuclear industry. Experimental and theoretical studies have revealed that helium bubbles have a detrimental effect on mechanical properties of nickel. However, the exact mechanism governing helium-induced embrittlement has not been properly explored. In the present work, the effect of various configurations of helium bubbles on the mechanical properties of nickel crystal has been investigated using atomistic simulations. The effect of various orientations of the crack plane and direction in the face centered cubic crystal of Ni was studied in conjunction with helium bubbles. In the three orientations of the crack, deformation was governed by Shockley and stair rod type dislocation in two of the orientations, while twinning and Lomer Cottrell locks govern the deformation in the third orientation. Despite the fact that helium bubbles reduce the strength of a single crystal of Ni containing a centrally embedded crack, an increase in the number of helium atoms has a negligible effect of the toughness of the material. Switching between the spatial coordinates of a helium bubble in front of the crack tip significantly affects the strength of the single crystal Ni. The results indicate that consideration of the geometry of the crystal along with modulation of helium clusters is an effective means to understand various defects in Ni crystals.